Scalable Creation of Deep Silicon‐Vacancy Color Centers in Diamond by Ion Implantation through a 1‐μm Pinhole. Issue 12 (17th October 2021) - Hunold, Lukas; Lagomarsino, Stefano; Flatae, Assegid M.; Kambalathmana, Haritha; Sledz, Florian; Sciortino, Silvio; Gelli, Nicla; Giuntini, Lorenzo; Agio, Mario
Abstract: The controlled creation of quantum emitters in diamond represents a major research effort in the fabrication of single‐photon devices. Here, the scalable production of silicon‐vacancy (SiV) color centers in single‐crystal diamond by ion implantation up to ≃ 1 μ m depths is presented. The lateral position of the SiV is spatially controlled by a 1‐ μ m pinhole placed in front of the sample, which can be moved nanometer precise using a piezo stage. The initial implantation position is controlled by monitoring the ion beam position with a camera. Hereby, silicon ions are implanted at the desired spots in an area comparable to the diffraction limit. The role of ions scattered by the pinhole and the activation yield of the SiV color centers for the creation of single quantum emitters is also discussed. Abstract : Diamond color centers represent a promising platform for quantum photonic applications. Different approaches for their localized creation in diamond have been developed, but they have been so far limited to shallow implantations. Here, the scalable production of silicon‐vacancy color centers at larger depths (down to 1 µm) and with a lateral precision of 1 µm is demonstrated.